Prophetic learning methods using props and their psychological impact on students - Fariadi AM, Ruslan (Psychology, Evaluation, and Technology in Educational Research, 2023)
The quality of learning outcomes is significantly influenced by selecting appropriate teaching methods tailored to the learners' circumstances. In imparting knowledge, Prophet Muhammad displayed a keen concern for employing teaching methods congruent with his students' characteristics. This study endeavors to elucidate the diverse teaching aids employed by Prophet Muhammad during the instructional process, his rationale behind the selection of these aids, and their resultant psychological impacts on the students. The research methodology employed in this investigation is Library Research, employing documentation techniques. The findings of this study reveal a plethora of teaching aids employed by Prophet Muhammad, with careful consideration given to the complexity of the subject matter, the unique characteristics of the learners, and their psychological dimensions. Indeed, it is irrefutable that teaching methods involving the use of teaching aids exert profound psychological effects on students, encompassing facets such as enjoyment, self-reliance, attention engagement, stimulation of curiosity, enhancement of assertiveness in expressing opinions, and facilitation of the realization of students' aspirations. The novelty of this research lies in its interdisciplinary approach, amalgamating facets of psychology, education, and religion to gain insight into the pedagogical methods of Prophet Muhammad. Furthermore, this research identifies an array of teaching aids employed by Prophet Muhammad, offering a wellspring of inspiration for developing innovative educational tools. Future research endeavors may be directed toward identifying the most efficacious and contextually relevant teaching aids for contemporary educational settings, thereby assisting educators in the judicious selection of teaching aids to enhance the overall quality of learning experiences.